Pengaruh Mikroorganisme terhadap Ketersediaan Nutrisi pada Tanaman Jagung : Kajian Literatur - Zebua, Tiesland; Lase, Natalia Kristiani; Telaumbanua, Putra Hidayat (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Soil microorganisms play an important role in increasing nutrient availability for maize plants through the processes of nitrogen fixation, phosphate solubilization, and humic acid production. These processes not only increase maize productivity but also reduce dependence on synthetic chemical fertilizers, thus supporting agricultural sustainability. This study explores the benefits of microorganisms such as Rhizobium, Azospirillum, Pseudomonas, and arbuscular mycorrhizal fungi in enhancing nutrient uptake, protecting plants from environmental stress, and improving soil quality. Challenges in the application of microorganism technology include adaptation to diverse environmental conditions and low farmer adoption. However, advances in genomic technology and biotechnology open up opportunities to optimize the benefits of soil microorganisms. The implementation of this microorganism-based technology has the potential to support efficient, environmentally friendly and sustainable maize farming.